Durabilitas Ac-Wc Sfesifikasi Bina Marga 2010 Menggunakan Pasir Alam Kampar Dengan Uji Rendaman Modifikasi Marshall - Sutazril, Mukhelnalis; Sentosa, Leo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
In Indonesia the weather condition has big influence on pavement performance and the reductionservice life. Moment happened by floods, repeatedly load repetation and seep water among asphalt and rock representing cause the happening of road pavement damage. The use of natural sand as fine aggregate in AC (Asphalt Concrate) mixture is limited to a minimum value of 15% oftotal of mixture weight. Evaluation from the aspect of utilization cost shows that natural sand is cheaper than fine aggregate from stone crushing process because of no extra cost for crushing. In this reseach, used specification of Bina Marga 2010 by using a variation of fine aggregate type ofsand for AC/WC fine gradation mixture. The variation used are 0%, 5%, 10%, 15%, 20%, 25%,and 30% of total aggregate mixture. Tests were performed using the Marshall test with differentimmersion time, i.e. Marshall standard, 1 day, 4 days, 7 days, and 28 days of immersion in the bath with the temperature of 600 C. The result show the variation of performance durability with the addition of natural sand content of 15% in optimum asphalt 6,25% has the smallest value of the first durability index with 6,70%, and durability performance of the mixture with the addition of natural sand content of 15% in optimum asphalt 6,25% has the smallest value of the second durability index with 15,70%. This mixture is more resistant (durable) to the effects of immersion in water.Keywords: natural sand, asphalt concrete AC / WC, Bina Marga Spesification 2010 and durability.